PEMANFAATAN TEKNOLOGI DALAM PENYELENGGARAAN PENDIDIKAN TERBUKA/JARAK JAUH (Jurnal TEKNODIK, 2019)
The idea of implementing Distance Education (DE) is to educationally serve the people who cannot be served by the existing face-to-face educational institutions due to one and some other reasons. Some of the constraints faced, as generally exposed, are in term of geographical distance and difficulty, transportation, time, limited budget, and physical disadvantages. In the very beginning stage, the learners of DE programs were adults. In the later development, DE institutions serve people not only adults but also those who are still at the school-age stage, from kindergarten to higher education. Not only the learners vary but also the technology/media used to deliver the learning contents, from the very old one (print technology) to the newest one (electronic technology). Currently many distance education institutions in developing countries use printbased technology as the main DE medium as the use of communications technologies is often cost-prohibitive. Almost all institutions in the Southeast Asian Countries that have already implemented distance education approach in their educational development still use print technology as a very important medium in delivering the programs. Even though some countries have used the internet technology as another potential alternative in delivering their distance learning contents. In this paper, the discussion will focus on the use of technologies in delivering distance learning contents, starting from print up to internet technologies.